Twelve-year trends in the prevalence and risk factors of diabetes and prediabetes in Turkish adults - (:unkn) unknown (SPRINGER, 2013)
There is concern about an emerging diabetes epidemic in Turkey. We aimed to determine the prevalence of diagnosed and undiagnosed diabetes, prediabetes and their 12-year trends and to identify risk factors for diabetes in the adult Turkish population. A cross-sectional, population-based survey, 'TURDEP-II' included 26,499 randomly sampled adults aged a parts per thousand yen 20 years (response rate: 87 %). Fasting glucose and biochemical parameters were measured in all; then a OGTT was performed to identify diabetes and prediabetes in eligible participants. The prevalence of diabetes was 16.5 % (new 7.5 %), translating to 6.5 million adults with diabetes in Turkey. It was higher in women than men (p = 0.008). The age-standardized prevalence to the TURDEP-I population (performed in 1997-98) was 13.7 % (if same diagnostic definition was applied diabetes prevalence is calculated 11.4 %). The prevalence of isolated-IFG and impaired glucose tolerance (IGT), and combined prediabetes was 14.7, 7.9, and 8.2 %, respectively; and that of obesity 36 % and hypertension 31.4 %. Compared to TURDEP-I; the rate of increase for diabetes: 90 %, IGT: 106 %, obesity: 40 % and central obesity: 35 %, but hypertension decreased by 11 % during the last 12 years. In women age, waist, body mass index (BMI), hypertension, low education, and living environment; in men age, BMI, and hypertension were independently associated with an increased prevalence of diabetes. In women current smoking, and in men being single were associated with a reduced risk. These results from one of the largest nationally representative surveys carried out so far show that diabetes has rapidly become a major public health challenge in Turkey. The figures are alarming and underscore the urgent need for national programs to prevent diabetes, to manage the illness and thus prevent complications.
Keywords: Diabetes mellitus; Impaired fasting glucose; Impaired glucose tolerance; Obesity; Hypertension; Clinical epidemiology; IMPAIRED GLUCOSE REGULATION; RENAL-DISEASE; MELLITUS; POPULATION; EDUCATION; EPIDEMIOLOGY; INTOLERANCE; TOLERANCE; HBA(1C); SAMPLE